2007
DOI: 10.1136/bmj.39301.497593.55
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in the home after the smoke-free legislation in Scotland: qualitative study

Abstract: Objective To explore the accounts of smokers and nonsmokers (who live with smokers) of smoking in their homes and cars after the Scottish smoke-free legislation; to examine the reported impact of the legislation on smoking in the home; and to consider the implications for future initiatives aimed at reducing children's exposure to secondhand smoke in the home. Design and setting A qualitative cross sectional study involving semistructured interviews conducted across Scotland shortly after the implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
3
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 20 publications
7
108
3
2
Order By: Relevance
“…Additional research is required to help clarify this discrepancy in the literature. One potential avenue for further investigation is to examine if inconsistencies in home smoking restrictions play a role in shaping youth beliefs about such restrictions; research has previously suggested that it is not uncommon for home smoking restrictions to be temporarily modified depending on circumstances [28].…”
Section: Discussionmentioning
confidence: 98%
“…Additional research is required to help clarify this discrepancy in the literature. One potential avenue for further investigation is to examine if inconsistencies in home smoking restrictions play a role in shaping youth beliefs about such restrictions; research has previously suggested that it is not uncommon for home smoking restrictions to be temporarily modified depending on circumstances [28].…”
Section: Discussionmentioning
confidence: 98%
“…Parents/carers appear willing to hear messages around smoke-free families and SHS, particularly if these messages can offer information on support services (i.e. SFS) and are positioned as part of a wider range of initiatives designed to improve the health and home environment of the child [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…While there is evidence that parents and carers may be imposing smoking restrictions inside their homes and asking visiting smokers to smoke outside [20,21], these restrictions may relax as children grow older or to avoid compromising strong emotional and social ties [22,23]. Research literature points towards the importance of trying to encourage parents/carers to stop smoking, or at least to taking their smoking outside of the home away from their children, to reduce SHS exposure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Estes dados são concordantes com outros estudos (Phillips et al, 2007) que revelaram que o (mau) cheiro do tabaco, a saúde (particularmente as preocupações em torno da saúde das crianças), a pressão mais ou menos ativa, para não fumar exercida por outros membros da família, e as preocupações sobre o efeito de modelagem foram as razões mais comuns para a que os fumadores convocam para não fumar em casa. No presente estudo, alguns dos entrevistados referiram a pressão exercida por outros familiares (cônjuges), mas nenhum referiu o efeito da modelagem (relação entre o consumo de tabaco dos pais e o dos filhos).…”
Section: Discussão E Conclusõesunclassified